2018
DOI: 10.3892/ijo.2018.4414
|View full text |Cite
|
Sign up to set email alerts
|

Matrine exerts inhibitory effects in melanoma through the regulation of miR-19b-3p/PTEN

Abstract: Matrine, one of the main alkaloid components extracted from the traditional Chinese herb, Sophora flavescens Ait, has various pharmacological effects, and has been reported to exert antitumor activity in melanoma. In the current study, the molecular mechanisms underlying the inhibitory effects of matrine were investigated in melanoma cell line. It was initially confirmed that matrine inhibited proliferation, invasion and induced apoptosis in human A375 and SK-MEL-2 melanoma cell lines in vitro. Subsequently, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Some studies have reported that miR-19b-3p regulates PTEN in some tumors Liu et al, 2018;Wei et al, 2018). We screened several candidate downstream target genes of miR-19b-3p and found that PTEN is one of them.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have reported that miR-19b-3p regulates PTEN in some tumors Liu et al, 2018;Wei et al, 2018). We screened several candidate downstream target genes of miR-19b-3p and found that PTEN is one of them.…”
Section: Discussionmentioning
confidence: 98%
“…It is often inactivated or mutated in many cancers; PTEN reverses the function of PI3K by dephosphorylation of PIP3 to form PIP2, thereby inhibiting the downstream AKT signal axis. Some studies have reported that miR-19b-3p regulates PTEN in some tumors Liu et al, 2018;Wei et al, 2018). Studies also have shown that PTEN regulates bone formation by inhibiting the PI3K/Akt signaling pathway during osteogenic differentiation of mouse embryonic stem cells and bone marrow mesenchymal stem cells (Huang et al, 2014;Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wei et al pointed out MAT declined the viability via the miR-19b-3p. 31 Li et al pointed out MAT exerted anti-carcinoma efficacy in prostate carcinoma via forkhead box O (FOXO). 32 Furthermore, Liao Li et al pointed out MAT restrained BC cells by up-regulating vascular endothelial growth factor (VEGF) and Wang et al pointed out LINC00472 could be a diagnostic marker in renal tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Take miR-19b-3p as an example: the up-regulated miR-19b-3p could inhibit apoptosis in renal tubular epithelial cells (Chen et al, 2019b) but inhibit the cell proliferation and contribute to the apoptosis in SH-SY5Y human neuroblastoma cells (Ma et al, 2016). The down-regulated miR-19b-3p in A375 cells and SK-MEL-2 melanoma cells was found to promote apoptosis (Wei et al, 2018). On the contrary, overexpression of miR-19b-3p could cause intracellular ROS accumulation in human aortic endothelial cells, leading to cellular apoptosis (Xue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%